The prevalence of Escherichia coli strains with extended spectrum beta-lactamases isolated in China - Liu, Haihong; Wang, Yueling; Wang, Gang; Xing, Quantai; Shao, Lihua; Dong, Xiaomeng; Sai, Lintao; Liu, Yongjuan; Ma, Lixian (Frontiers in Microbiology, 2015)
The extended-spectrum-lactamases-producing Escherichia coli has rapidly spread worldwide. Escherichia coli has been becoming much more resistant to β-lactam antibiotics and other commonly available antimicrobials. We investigated the prevalence, resistance, and probable gene type of ESBLs using MICs testing and polymerase chain reaction. We have collected 289 single-patient E. coli Isolates based on samples of China from July 2013 to August 2014. This article explored that the prevalence of ESBL-producing Isolates showed multi-resistant to antimicrobials such as fluoroquinolones, trimethoprim, tetracycline and aminoglycosides, and so on. The frequencies of resistance in Isolates were as follows: Ciprofloxacin, 74%, gentamicin, 69.5%, levofloxacin, 63%, tobramycin, 39%, and minocyline, 7.9%. According to our results, 197(68.2%) of the total 289 Isolates were ESBL-producing strains; further, 172 (87.3%) producers contained genes encoding CTX-M enzymes and 142(72.1%) producers contained genes encoding TEM enzymes. Most ESBL-producing Escherichia coli has produced more than one type of beta-lactamase. Nucleotide sequence analysis has revealed the diversity of ESBLs types: CTX-M -15 is in the majority and TEM-135, CTX-M-3, CTX-M-98, CTX-M-14, CTX-M-142, CTX-M-65, CTX-M-55, CTX-M-27 and CTX-M-123 have been recovered. The results confirm that ESBL producers which are common in hospital strains of Escherichia coli are resistant to cephalosporins and other antibiotics in China. It is important to monitor such strains closely and provide scientific evidence of rational application of antibiotics to prevent their spread.